1980
DOI: 10.1159/000225492
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Design of Anticancer Chemotherapy

Abstract: Recent advances in the rational design of anticancer chemotherapy in this laboratory have been based on strategic differences between normal and cancer cells. On the basis of our identification of quantitative biochemical markers and characteristic enzymic and metabolic programs of neoplastic cells, we have designed single and combination drug treatments. This chemotherapeutic approach aims at specific enzymic targets in cancer cells that are closely linked with transformation and progression. With the identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Early studies have demonstrated a positive correlation between the enzymatic activity of RNR and the rate of proliferation of transplanted Novikoff carcinomas (11,12). Thus, because of its critical role in the de novo synthesis of DNA, RNR is considered to be a potential target for the development of cancer chemotherapeutic agents.…”
mentioning
confidence: 99%
“…Early studies have demonstrated a positive correlation between the enzymatic activity of RNR and the rate of proliferation of transplanted Novikoff carcinomas (11,12). Thus, because of its critical role in the de novo synthesis of DNA, RNR is considered to be a potential target for the development of cancer chemotherapeutic agents.…”
mentioning
confidence: 99%